2021
DOI: 10.1088/1748-9326/abbfc3
|View full text |Cite
|
Sign up to set email alerts
|

Global water scarcity including surface water quality and expansions of clean water technologies

Abstract: Water scarcity threatens people in various regions, and has predominantly been studied from a water quantity perspective only. Here we show that global water scarcity is driven by both water quantity and water quality issues, and quantify expansions in clean water technologies (i.e. desalination and treated wastewater reuse) to ‘reduce the number of people suffering from water scarcity’ as urgently required by UN’s Sustainable Development Goal 6. Including water quality (i.e. water temperature, salinity, organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
154
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(162 citation statements)
references
References 67 publications
5
154
1
2
Order By: Relevance
“…Global water scarcity is driven by water quality issues (water temperature, salinity, organic pollution and nutrients), and polluted return flows degrade water quality and exacerbate water scarcity. Technical and economic constraints of expanding desalination and treated wastewater reuse across the world still exist and water purification treatment is confronted with more challenges [ 2 ]. Natural organic matter (NOM, which includes DOM and particulate organic matter) is a key material in sustaining all biogeochemical processes and phenomena in ecosystems [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global water scarcity is driven by water quality issues (water temperature, salinity, organic pollution and nutrients), and polluted return flows degrade water quality and exacerbate water scarcity. Technical and economic constraints of expanding desalination and treated wastewater reuse across the world still exist and water purification treatment is confronted with more challenges [ 2 ]. Natural organic matter (NOM, which includes DOM and particulate organic matter) is a key material in sustaining all biogeochemical processes and phenomena in ecosystems [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are over one billion individuals that do not have access to safe drinking water Boretti & Rosa (2019). Nearly half of the world's people will reside in water-stressed environments by 2030 van Vliet et al (2021). Nearly all, tropical countries have high relative humidity, average annual rainfall, ambient temperature and solar irradiance and are classified as humid countries Han et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…The result shows that 16.8 mL/h of water was collected by using TE-D at humidity level of 82%. The new hot heat sink with a rectangular fin array was built by Udomsakdigool et al (2007) for TE-D system and they concluded that the performance was 95 percent and COP of TE-D was 0.88 at 12 V voltage and 1.9 A electric current. Joshi et al (2017) investigated TE-D made up of ten TEM and of 0.7 m long.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is crucial to observe the spatial and temporal variation in water availability (and its demand), which leads to water stress in various parts of the world during distinct times of the year. Several studies assess water stress in different parts of the world, and most of these studies adopted an annual scale for their assessments (Liu et al, 2017, Van Vliet et al, 2021. Studies suggest that high water scarcity is observed in locations with either large population density or the existence of highly irrigated agriculture or their combination (Boretti & Rosa, 2019;Status et al, 2021).…”
Section: Introductionmentioning
confidence: 99%